Erjingwan and Alzheimer’s disease: research based on network pharmacology and experimental confirmation - Xu, Yuya; Zhang, Jian; Li, Xuling (Frontiers in Pharmacology, 2024)
Background: Alzheimer's disease (AD), a challenging neurodegenerative condition, has emerged as a significant global public health concern. The Chinese medicine decoction Erjingwan (EJW) has shown promising efficacy in AD treatment, though its mechanism remains unclear.Objective: This study aims to elucidate the mechanism by which EJW treats AD through network pharmacology analysis and in vivo experiments.Methods: We identified EJW's components using the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database and determined AD-related targets from various databases. A network comprising herbs-compounds-targets was established, and EJW's core targets were ascertained through protein-protein interaction (PPI) analysis. This study assessed the cognitive abilities of APP/PS1 mice using Morris water mazes and Y mazes, in addition to analyzing blood samples for triglyceride (TG), total cholesterol (TC), low-density lipoprotein (LDL), and high-density lipoprotein (HDL) levels. Brain tissues were examined histologically with HE staining, Nissl staining, and immunohistochemistry (IHC) for amyloid β-protein (Aβ) detection. Superoxide dismutase (SOD), reactive oxygen species (ROS), Interleukin-1β (IL-1β), and Interleukin-6 (IL-6) levels in the hippocampal region were measured by ELISA.mRNA expression of apolipoprotein A-I (APOA-I), apolipoprotein B (APOB), apolipoprotein E4 (APOE4), advanced glycation end products (AGE), the receptor for AGE (RAGE), and nuclear factor kappa-B (NF-κB) was evaluated by quantitative PCR (q-PCR). Western blotting was used to detect the expression of AGE, RAGE, NF-κB, and Tau protein.Results: Screening identified 57 chemical components and 222 potential targets of EJW. Ten core targets for AD treatment were identified, with enrichment analysis suggesting EJW's effects are related to lipid metabolism and AGEs/RAGE pathways. EJW enhanced learning and memory in APP/PS1 mice, protected neuronal structure in the hippocampal region, reduced Aβ deposition, and altered levels of TG, TC, LDL, IL-1β, and IL-6, and the expression of APOE4, AGEs, RAGE, NF-κB, and Tau protein, while increasing SOD, APOA-I, and APOB mRNA expression.Conclusions: The study identified four core components of EJW—iosgenin, baicalein, beta-sitosterol, quercetin—and ten core targets including AKT1, IL6, VEGFA, TP53, CASP3, for treating AD. Experimental results demonstrate EJW's capacity to modulate lipid profiles, reduce pathological markers such as Aβ1-42, Tau, IL-6, IL-1β, ROS, SOD, and enhance cognitive functions in APP/PS1 mice, potentially through inhibiting the AGEs/RAGE/NF-κB pathway.